Effects of a commercially formulated glyphosate solutions at recommended concentrations on honeybee (Apis mellifera L.) behaviours - Qi-Hua Luo (Nature Portfolio, 2021)
Abstract Glyphosate, the active ingredient of the most widely used commercial herbicide formulation, is extensively used and produced in China. Previous studies have reported sublethal effects of glyphosate on honeybees. However, the effects of commercially formulated glyphosate (CFG) at the recommended concentration (RC) on the chronic toxicity of honeybees, especially on their behaviours, remain unknown. In this study, a series of behavioural experiments were conducted to investigate the effects of CFG on honeybees. The results showed that there was a significant decline in water responsiveness at 1/2 × , 1 × and 2 × the RC after 3 h of exposure to CFG for 11 days. The CFG significantly reduced sucrose responsiveness at 1/2 × and 1 × the RC. In addition, CFG significantly affected olfactory learning ability at 1/2 × , 1 × , and 2 × the RC and negatively affected memory ability at 1/2 × and 1 × the RC. The climbing ability of honeybees also significantly decreased at 1/2 × , 1 × and 2 × the RC. Our findings indicated that, after they were chronically exposed to CFG at the RC, honeybees exhibited behavioural changes. These results provide a theoretical basis for regulating field applications of CFG, which is necessary for establishing an early warning and notification system and for protecting honeybees.